Comparison of Reinforced Concrete Structures Using Local Spectral Response Analysis, Indonesian Spectral Design and SNI 1726-2019 - Sakul, Verrent Ecclesia; Sumajouw, Marthin Dody Josias; Manoppo , Fabian Johanes (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
In planning earthquake-resistant building structures, especially in areas with a high seismic risk, it is crucial to consider earthquake resilience factors. Maximum ground acceleration and spectral response are seismic parameters used to design buildings in accordance with the provisions of the Indonesian National Standard (SNI) 1726-2019 regarding earthquake-resistant building design. The spectral response values used for the comparison of reinforced concrete structures include the Local Spectral Response calculated using the Probabilistic Seismic Hazard Analysis (PSHA) method with the assistance of EZ-FRISK software, the spectral response value from Spektra Design Indonesia, and SNI 1726:2019. The results of soil classification indicated that the soil layer at the research site was of medium type; therefore, the structural components of the Special Moment Resisting Frame System (SRPMK) were designed accordingly. Building modeling and analysis were conducted using ETABS version 19 software. Based on the results of the PSHA analysis, the Peak Ground Acceleration (PGA) value for the 2500-year earthquake recurrence period for the Local Spectral Response was 0.7233 g, and the spectral response value was 0.8473 g. The comparative analysis of reinforced concrete structures using the Local Spectral Response value revealed that some structural components experienced shear failure, particularly around openings such as stairwells. In contrast, the analysis using the Indonesian Spectral Design and SNI 1726:2019 indicated that the structural components could withstand the shear forces acting on the cross-sections.